EQUIPMENT OF FACILITIES AND INFRASTUCTURE IN AUTOMOTIVE WORKSHOPS ACCORDING TO STUDENT PERCEPTIONS - Hendrawan (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2022)
This study aims to determine how big the level of feasibility of suggestions in practical workshops. In addition, it is also to find out how big the level of infrastructure feasibility is in the practical workshop. The type of method used in this research is to use descriptive research which in its approach is carried out with a data collection process through observation (data observation), documentation, and interviews with workshop techniques, lecturers who teach in the automotive field as a valid data source. Based on the results of the research on the feasibility of facilities and infrastructure at the automotive workshop according to students' perceptions that the results of the reliability/constraint aspect are 80% in the very feasible category for the lowest feasibility achievement results are accessibility, which is 28% in the quite feasible category and 50% assurance/assurance in the category quite decent. Meanwhile, for the other results, 71% of facilities and media are in the appropriate category and empathy is 100 feasible.